Política y redes sociales: el sentido del sinsentido (Monográfico) - Moreno Vega, Bernardo (2023)
This work intends to problematize two disciplines of the social sciences such as politics and communication, showing -as a hypothesis- how, paradoxically, social networks, instead of generating a public sphere that strengthens democracy, dilute their forms and trivialize their contents. Since the last general elections of 2021, this story in Ecuador has been expressed on a national and local scale, emptying both political campaigns and the exercise of popularly elected positions of content. However, it is precisely this hollowing out that is giving a new meaning to politics and communication. Are social networks mirages that shield politicians from their specific responsibilities, endorsing citizens to manage the problems of an underlying reality? That is the question that will guide this work. To try to give an answer, we will approach this problem through a dialogue between sociology and political communication, taking the contributions of Bauman and Donskis on liquid modernity, as well as Jaime Durán Barba and Santiago Nieto regarding of the role of virtuality in the reconfiguration of politics, which -in our opinion- shed important light on the current state of affairs. We hope that this document contributes to generating a long-term reflection in the search for the meaning of the apparent “nonsense” that social networks such as Facebook, WhatsApp, Instagram or Tik Tok are printing on politics and communication.